Paradise Lost - McColley, Grant (Harvard theological review, 1939)
Among the significant questions perennially raised by Miltonic criticism, the two most important are the two most variously answered: What is Paradise Lost, and why did Milton write it? If the evidence which follows may be regarded as sufficiently exhaustive, I suggest that Paradise Lost was designed as a non-sectarian epic and more or less deliberately modelled as well as based upon conservative religious literature. The second conclusion is that Milton wrote his greatest poem to justify the ways of the Christian God, and to give artistic-prophetic expression to beliefs which were both vital and sacred to him.